Assessment of Some Risk Factors Associated with Cancer - عساف, عبير (Latakia University Journal -Medical Sciences Series, 2021)
Cancer alone kills 7.6 million people every year. According to World Health Organization (WHO) estimates, cancer deaths in the Eastern Mediterranean Region will increase from 9.4% in 2015 to 12.3% in 2030 of all deaths. These estimates are based on the impact of population growth and aging, as well as increased exposure to factors that increase the incidence of cancer, such as smoking, unhealthy diet, physical inactivity, alcoholism and environmental pollution, which will lead to a higher burden of cancer. Therefore, the current descriptive study was conducted to assess some of the risk factors associated with cancer. This study was applied to a sample of 100 cancer patients available in the Oncology Department at Tishreen University Hospital in Lattakia city. A questionnaire developed by the researcher was used for this purpose. The results showed that there are many risk factors that can be prevented, the most important of which are smoking, eating secreted meals, preserving food in plastic containers, and the presence of communication towers next to places of residence or work. The study recommended the necessity of conducting health education sessions about cancer and predisposing risk factors, activating the role of institutions and organizations in preventing risk factors, and conducting other research at the republic level.